Hyperfine splitting of [Al VI] 3.66 μm and the Al isotopic ratio - Casassus, S; Storey, P; Barlow, M; Roche, P (2005)
Spectra of [Al VI] 3.66 μm 3P 2 ← 3P 1 in the coronal region of PN NGC 6302, obtained with Phoenix on Gemini-South at resolving powers of up to 75000, resolve the line into five hyperfine components separated by 20 to 60 km s -1 due to the coupling of the I = 5/2 nuclear spin of 27Al with the total electronic angular momentum J. 26Al has a different nuclear spin of I = 5, and a different hyperfine structure (HFS), which allows us to place a 3 σ upper limit on the 26Al/ 27Al ratio of 1/33. We measure the HFS magnetic-dipole coupling constants for [Al VI], and provide the first observational estimates of atomic electric-quadrupole HFS coupling constants. © 2005 American Institute of Physics.